2007
DOI: 10.2174/157339407780126647
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Profiling of Prostate Cancer: Implications for Future Therapy

Abstract: Prostate cancer is predicted to be the most common cancer diagnosed in American men in 2006 with an estimated 230,000 new cases in the United States alone [1]. It is likely to result in over 27,000 deaths in 2006, and the average male will have a one in six chance of developing this malady in his lifetime [1]. These statistics illustrate the need to have screening and treatment systems in place that possess both a high degree of sensitivity as well as proven effectiveness. With the recent strides made in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…All of these results strongly suggest that activation of ␤-catenin signaling may be associated with the progression of the disease through signaling cross-talk. Thus, our study can open a new avenue in the combinatorial therapeutic approach which is currently under development in cancer treatment (42,51,52).…”
Section: Discussionmentioning
confidence: 89%
“…All of these results strongly suggest that activation of ␤-catenin signaling may be associated with the progression of the disease through signaling cross-talk. Thus, our study can open a new avenue in the combinatorial therapeutic approach which is currently under development in cancer treatment (42,51,52).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have revealed that cannabinoids have an effect on the expression of VEGF, which is one of the major cancer cell-released chemoattractants in tumor neovascularization [100]. Met-F-AEA has been shown to decrease levels of VEGF and VEGFR-1 in K-ras-transformed thyroid cells and in experimental tumors of xenografted nude mice [90].…”
Section: Cb1 and Cb2 Mediated Anti-proliferative And Apoptotic Effmentioning
confidence: 99%
“…at ASPET Journals on May 12, 2018 jpet.aspetjournals.org endothelial growth factor (VEGF), which is one of the major cancer cell-released chemoattractants in tumor neovascularization (for review, see Saia et al, 2007). Met-F-AEA was demonstrated to decrease levels of VEGF and VEGFR-1 in K-ras-transformed thyroid cells and in experimental tumors of nude mice xenografted with these cells (Portella et al, 2003).…”
mentioning
confidence: 99%